Ultrasonic Manifestations of Mesenteric Inflammatory Myofibroblastic Tumors in Children - Qian, Jingjing; Zhu, Kun; Ye, Jingjing (Frontiers in Pediatrics, 2019)
Objective: To explore the ultrasonic manifestations of mesenteric inflammatory myofibroblastic tumors (IMTs) in children. Methods: Seven patients with mesenteric IMTs were retrospectively analyzed. The ultrasonic manifestations, such as the locations, sizes, morphology, borders, internal echo, blood flow, and metastasis, of the tumors were detected. Results: In all the seven pediatric patients, a solitary lesion was found for the mesenteric IMTs, including five cases in the ileocecal mesentery and two cases in the mesentery of ascending colon. All the single tumors were revealed as irregular hypoechoic masses with uneven internal echoes and enhanced echoes in the surrounding intestine and omentum. Internal blood flow signals were enriched in the tumors. The borders were clear in five cases and unclear in two cases. In addition, two cases had peritoneal effusion and one case had calcified plaques. In the follow-up studies, one of the seven IMT patients had malignant transformation, and one case was transferred to the pelvic cavity. Conclusion: Ultrasonic examination can clearly demonstrate the locations, sizes, morphology, borders, internal echo, blood flow as well as metastasis of the pediatric IMT of the mesentery, having an important clinical application value as an adjunct to computed tomography (CT).